PENGARUH RASIO AKTIVITAS, PERTUMBUHAN ASET DAN UKURAN PERUSAHAAN TERHADAP REAKSI PASAR - Fadhilah; Neneng Hasanah (Jurnal Nusa Akuntansi, 2026)
This study was conducted with the aim of testing and analyzing the influence of activity ratio, asset growth, and company size on market reactions. This study uses a quantitative approach that emphasizes objective measurement aspects of social phenomena. Data collection techniques use documentation techniques or indirect observation. This study is included in the secondary research category, namely research that aims to determine the influence between two variables. Secondary data in this study comes from the annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The population used in this study is energy sector companies listed on the Indonesia Stock Exchange (IDX) with a reporting period of 2019 to 2023. The sampling technique in this study used purposive sampling, with a total of 65 sample data from 13 companies that met the research criteria. The analytical method used in this study is descriptive statistical analysis with the classical assumption test, the coefficient of determination test, and the partial t-test. By using multiple linear regression analysis. Data testing was conducted using Microsoft Excel and Statistic Eviews version 13 software. The results of this study indicate that the Activity Ratio, Asset Growth, and Company Size simultaneously influence market reaction. However, partially, the Activity Ratio has a significant effect on market reaction, while Asset Growth and Company Size do not.